CONTRAST MAGNETIC RESONANCE INVESTIGATION IN PATIENTS AFTER MYOCARDIAL INFARCTION AND TACHIARRHYTHMIAS - V. Yu. Usov; V. E. Babokin; O. V. Mochula; M. S. Khlynin; P. I. Lukyanenok; T. A. Shelkovnikova; E. E. Borodina; I. O. Kurlov; A. I. Petsh; R. E. Batalov (Российский кардиологический журнал, 2014)
We present the results of MRI study of the heart with paramagnetic contrasting for visualization of the foci of myocardial damage, that lead to atrial tachiarrhythmias in patients with severe infarction of the left ventricle. It is shown that the volume of the left atrium more than 75 cm3 and accumulation of paramagnetic contrast in atrial myocardium with the enhancement T1-adj. spin-echo regimen index more than 1,27 are prognostic factors for atrial tachiarrhythmias, and MRI of the heart with contrast is an important additional method of patients’ investigation with atrial rhythm disorders.